2019
DOI: 10.1186/s12888-019-2274-5
|View full text |Cite
|
Sign up to set email alerts
|

‘Walk this way’: results from a pilot randomised controlled trial of a health coaching intervention to reduce sedentary behaviour and increase physical activity in people with serious mental illness

Abstract: Background Cardiovascular disease (CVD) is the leading cause of premature death among people with serious mental illness (SMI). Sedentary behaviour (SB) is an independent risk factor for CVD and mortality and people with SMI are highly sedentary. We developed a health coaching intervention called ‘Walk this Way’ to reduce SB and increase physical activity (PA) in people with SMI and conducted a pilot randomised controlled trial (RCT) to test its feasibility and acceptability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 40 publications
2
47
0
Order By: Relevance
“…All included studies were published in the last 10 years (2010 to 2019), with the majority originating after 2017 (n = 10). Six studies included a follow-up measure 7 to 40 weeks post-intervention (Thomsen et al, 2019;Biddle et al, 2020;De Greef et al, 2010;De Greef et al, 2011;Williams et al, 2019;Ryan et al, 2019). All studies were written in the English language and could be categorised in five clinical population groups, including overweight/obesity (n = 6), (pre) diabetes mellitus type 2 (T2DM, n = 4), cardiovascular diseases (CVD; n = 4), neurological and cognitive disorders (n = 2) and musculoskeletal disorders (n = 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included studies were published in the last 10 years (2010 to 2019), with the majority originating after 2017 (n = 10). Six studies included a follow-up measure 7 to 40 weeks post-intervention (Thomsen et al, 2019;Biddle et al, 2020;De Greef et al, 2010;De Greef et al, 2011;Williams et al, 2019;Ryan et al, 2019). All studies were written in the English language and could be categorised in five clinical population groups, including overweight/obesity (n = 6), (pre) diabetes mellitus type 2 (T2DM, n = 4), cardiovascular diseases (CVD; n = 4), neurological and cognitive disorders (n = 2) and musculoskeletal disorders (n = 2).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies met either two (n: 5) (De Greef et al, 2010;De Greef et al, 2011;Ryan et al, 2019;Laslovich et al, 2019;Lyons et al, 2017) or one (n: 3) (Biddle et al, 2020;Paul et al, 2016;Prince et al, 2018) of the six risk of bias criteria. However, 13 studies provided insufficient information to assess three (n: 3) (Kozey Keadle et al, 2014;MacEwen et al, 2017;Yang et al, 2017), two (n: 4) (Paul et al, 2016;English et al, 2016;Holliday et al, 2020;Miyamoto et al, 2017) and one (n: 6) (Thomsen et al, 2017;Biddle et al, 2020;Williams et al, 2019;Laslovich et al, 2019;Carr et al, 2013;Thomsen et al, 2016) risk of bias criteria. Although a selection bias could be precluded in all studies, five studies did not describe the concealment procedure in sufficient detail.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Prior studies of health coaching interventions have shown coaching to be effective in promoting health behavior change and improving some health outcomes. 10 12 , 33 In particular, coaching toward a defined purpose to facilitate health behavior change—for example, tobacco cessation, 34 , 35 increasing physical activity, 12 , 36 , 37 or improving diet and weight management 11 ,12 —often results in a significant, measurable impact. However, unlike many coaching programs (and other health behavior interventions), the broad aims of Whole Health Coaching are not defined in advance; they are instead defined by participants in the course of the coaching relationship.…”
Section: Discussionmentioning
confidence: 99%
“…As we know there will be participants who drop out of the study, we will recruit 120 participants—60 in the intervention group and 60 in the control group to account for this drop out. We are basing this dropout rate partly on a pilot study undertaken with this population evaluating an intervention to support people to be more physically active [ 20 ]. This sample size is used due to the resources of the study.…”
Section: Methods and Analysismentioning
confidence: 99%